Human Adenovirus Subtype 21a Isolates From Children With Severe Lower Respiratory Illness in China - Liu, Wenkuan; Zhang, Li; Cai, Yong; Zhang, Qiong; Chen, Dehui; Qiu, Shuyan; Wang, Yanqun; Xu, Duo; Gu, Shujun; Li, Xiao; Dai, Jing; Liu, Qian; et al. (Frontiers in Microbiology, 2022)
Human adenovirus type 21 (HAdV-21) is an important pathogen associated with acute respiratory infection (ARI), but it was rarely reported and characterized so far. In this study, 151 of 1,704 (8.9%) pediatric patients (≤14 years old) hospitalized with ARI in Guangzhou, China in 2019 were positive for HAdV which was the third most frequently detected pathogen. Two HAdV-21-positive patients presented with severe lower respiratory illness and had similar initial symptoms at onset of illness. Then two HAdV-21 strains were isolated and characterized. The two HAdV-21 strains were sequenced and classified as subtype 21a with genomes closely related to strain BB/201903 found in Bengbu, China in March 2019. Phylogenetic analysis for whole genome and major antigen proteins of global HAdV-21 strains showed that HAdV-21 could be classified into two branches, branch 1 including genotype 21p, branch 2 including all other strains dividing into genotype 21a and 21b. There was no significant difference in the plaque size, or the replication curves between the two HAdV-21a strains and the prototype strain HAdV-21p AV-1645. However, there were five highly variable regions (HVR1, HVR3, HVR4, HVR5, and HVR7) in the hexon protein that varied between two branches. Mice immunized with one branch strain showed 2–4-fold lower neutralizing antibody titers against another branch strain. In summary, this study firstly reported two HAdV-21a infections of children in China, characterized two isolates of HAdV-21a associated with severe lower respiratory illness; our results could be important for understanding the HAdV-21 epidemiology and pathogenic, and for developing HAdV-21 vaccine and drug.